Health Risk Analysis of Lead Exposure from Fish Consumption among Communities along Youtefa Gulf, Jayapura - Hasmi; Mallongi, Anwar (Pakistan Journal of Nutrition, 2016)
Background: Human life is threatened by environmental hazards due to toxic contamination with lead. According to some studies, the waters and biota of Youtefa Gulf near Jayapura city have been polluted by lead. Objective: This study aimed to analyze the health risks caused by lead exposure from consuming fish and the non-carcinogenic risk of consuming fish for the citizens of Youtefa Gulf. The study used observational research with a risk analysis approach (Risk Quotient (RQ)). Methodology: The study population included fish and people living along Youtefa Gulf in Jayapura, with a sample composed of 75 people and fish collected from 12 stations. Samples were collected by purposive sampling. Results: The results showed that the concentrations of Pb in the fish from the12 stations was an average of 2.46 mg kg–1, a level considered to indicate pollution because it is above the 0.3 mg kg–1 threshold defined by ISO 7387 in the year 2009. Out of the 75 respondents, 66 respondents (88%) were found to have an RQ>1, which is considered to indicate high risk of lead exposure because it is greater than 1. From the results, the average RQ from the 75 respondents who consumed fish was 6.03. Based on this very high RQ value, the risk for these individuals needs to be controlled. Conclusion: It is recommended that the Youtefa Gulf community reduce its exposure to lead by decreasing the amount of fish consumed and decreasing the duration of daily lead exposure to diminish the health effects caused by exposure to lead-contaminated fish.